Immobilized liquid layers: A new approach to anti-adhesion surfaces for medical applications. Issue 9 (May 2016) - Sotiri, Irini; Overton, Jonathan C; Waterhouse, Anna; Howell, Caitlin
Surface fouling and undesired adhesion are nearly ubiquitous problems in the medical field, complicating everything from surgeries to routine daily care of patients. Recently, the concept of immobilized liquid (IL) interfaces has been gaining attention as a highly versatile new approach to antifouling, with a wide variety of promising applications in medicine. Here, we review the general concepts behind IL layers and discuss the fabrication strategies on medically relevant materials developed so far. We also summarize the most important findings to date on applications of potential interest to the medical community, including the use of these surfaces as anti-thrombogenic and anti-bacterial materials, anti-adhesive textiles, high-performance coatings for optics, and as unique platforms for diagnostics. Although the full potential and pitfalls of IL layers in medicine are just beginning to be explored, we believe that this approach to anti-adhesive surfaces will prove broadly useful for medical applications in the future.